2015
DOI: 10.15361/1984-5529.2016v44n1p102-112
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the predictive criteria for the tropical fruit tree nutritional status

Abstract: The diagnosis of plant nutritional status that aims to balance essential elements in the plant is of utmost importance for sustainable agriculture. Nutritional diagnosis is a technique that has been implemented to maximize the economic return from fertilization and minimize losses to the environment. A balance can be defined as a relationship between components interacting in plant tissue, where some nutrients may be present in excess, deficiency or sufficiency. Diagnostic methods have been evolving constantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
1
11
0
5
Order By: Relevance
“…Sharpe et al (1989) reported that the nutritional status assessed at different times affected the nutrient balance of the peach tree grown in the United States. This concurs with observations made under Brazilian conditions for guava cultivation (Rozane et al, 2015b). However, at the same time, the assessment of the nutritional status of a crop under similar edaphoclimatic conditions reveals divergences in the nutritional balance within the crop when variations are present in the cultivar/variety, as reported by Parent et al 2013b However, although divergences between the nutritional patterns of each species, cultivar and edaphoclimatic cultivation condition are evident, the similarities in the nutritional patterns among the genotypes should also be taken into consideration (Parent et al, 2013a;Rozane et al, 2015a).…”
Section: Introductionsupporting
confidence: 93%
“…Sharpe et al (1989) reported that the nutritional status assessed at different times affected the nutrient balance of the peach tree grown in the United States. This concurs with observations made under Brazilian conditions for guava cultivation (Rozane et al, 2015b). However, at the same time, the assessment of the nutritional status of a crop under similar edaphoclimatic conditions reveals divergences in the nutritional balance within the crop when variations are present in the cultivar/variety, as reported by Parent et al 2013b However, although divergences between the nutritional patterns of each species, cultivar and edaphoclimatic cultivation condition are evident, the similarities in the nutritional patterns among the genotypes should also be taken into consideration (Parent et al, 2013a;Rozane et al, 2015a).…”
Section: Introductionsupporting
confidence: 93%
“…A likely explanation may be associated with no water restriction in the period, which allows constant flow of nutrients especially for mass flow, the primary means of conduction nutrients to plants as reported by Malavolta (2006) and Oliveira et al (2010), in addition, in the winter, there is a greater accumulation of Degrees-days due to the lower incidence of radiation, thus reducing the photosynthetic efficiency of this plant (TAULYA et al, 2014). This allowed greater accumulation of nutrients in the leaves of both varieties observed in Tables 3 and 6; Rozane et al (2016) indicate that climatic conditions and different periods of harvest of the diagnostic leaf, even though of the same species, provide significant nutritional variations in the nutritional balance of the diagnostic leaf, which ensures that it is reflected in the data of tables 3 and 6 since the nutrients generally tend to migrate to the bunch from stage 4.…”
Section: Resultsmentioning
confidence: 74%
“…The CND based on clr aimed initially to replace DRIS for regional diagnosis [16,42,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Thereafter, a website service was made available to Brazilian growers (https://www.registro.unesp.br/#!/sites/cnd/).…”
Section: Tissue Nutrient Diagnosismentioning
confidence: 99%